The impact of status and social context on health service co-design: an example from a collaborative improvement initiative in UK primary care - Litchfield, I; Bentham, L; Hill, A; McManus, R; Lilford, R; Greenfield, S (BioMed Central, 2018)
Background Increasingly, collaborative participatory methods requiring open and honest interaction between a range of stakeholders are being used to improve health service delivery. To be successful these methodologies must incorporate perspectives from a range of patients and staff. Yet, if unaccounted for, the complex relationships amongst staff groups and between patients and providers can affect the veracity and applicability of co-designed solutions. Methods Two focus groups convened to discuss suggestions for the improvement of blood testing and result communication in primary care. The groups were mixed of patients and staff in various combinations drawn from the four participating study practices. Here we present a secondary mixed-method analysis of the interaction between participants in both groups using sociogrammatic and thematic analysis. Results Despite a similar mix of practice staff and patients the two groups produced contrasting discussions, seemingly influenced by status and social context. The sociograms provided a useful insight into the flow of conversation and highlighted the dominance of the senior staff member in the first focus group. Within the three key themes of social context, the alliances formed between participants and the fluidity of the roles assumed manifested differently between groups apparently dictated by the different profile of the participants of each. Conclusions For primary care service improvement attention must be paid to the background of participants when convening collaborative service improvement groups as status and imported hierarchies can have significant connotations for the data produced.